2018
DOI: 10.1177/1938965518777223
|View full text |Cite
|
Sign up to set email alerts
|

How Changes in the House Advantages of Reel Slots Affect Game Performance

Abstract: In two-game pairings of otherwise identical reel slot machines, the games with greater pars outperformed those with lesser pars. This finding held across five pairings, three casinos, three gaming markets, three game titles, three differences in pars, and five bank locations. These findings help clarify an important and polarizing issue within the literature and among casino operators. Many believe that increasing pars would be perceived as increasing prices, potentially driving customers to competitors. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
37
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(54 citation statements)
references
References 9 publications
(25 reference statements)
14
37
3
Order By: Relevance
“…Without naming it expressly, many have argued that the law of demand can be applied to reel slot play, holding that gamblers eventually detect the par (price) and subsequently decrease play on the high-par games (Frank, 2017; Gallaway, 2014; Legato, 2015, 2019; Meczka, 2017). To the contrary, the price shocks in previous research of a similar design have not produced support for the law of demand (Lucas, 2019; Lucas & Brandmeir, 2005; Lucas & Spilde, 2019a, 2019b). Furthermore, at the level of the clientele, the responses to these previous price shocks would not be considered rational, within the context of the generalized axiom of revealed preference (i.e., GARP).…”
Section: Literature Reviewmentioning
confidence: 82%
See 4 more Smart Citations
“…Without naming it expressly, many have argued that the law of demand can be applied to reel slot play, holding that gamblers eventually detect the par (price) and subsequently decrease play on the high-par games (Frank, 2017; Gallaway, 2014; Legato, 2015, 2019; Meczka, 2017). To the contrary, the price shocks in previous research of a similar design have not produced support for the law of demand (Lucas, 2019; Lucas & Brandmeir, 2005; Lucas & Spilde, 2019a, 2019b). Furthermore, at the level of the clientele, the responses to these previous price shocks would not be considered rational, within the context of the generalized axiom of revealed preference (i.e., GARP).…”
Section: Literature Reviewmentioning
confidence: 82%
“…Other studies that have featured paired designs have found increases in the pars of low-denomination games to be associated with significant increases in T-win (Lucas, 2019; Lucas & Spilde, 2019a, 2019b). These increases were also economically significant, ranging from 48.66% to 236.45% above the T-win levels produced by the low-par games.…”
Section: Literature Reviewmentioning
confidence: 98%
See 3 more Smart Citations